2016
DOI: 10.22237/jmasm/1462077000
|View full text |Cite
|
Sign up to set email alerts
|

Application of Esscher Transformed Laplace Distribution in Microarray Gene Expression Data

Abstract: Microarrays allow the study of the expression profile of hundreds to thousands of genes simultaneously. These expressions could be from treated samples and the healthy controls. The Esscher transformed Laplace distribution is used to fit microarray expression data as compared to Normal and Laplace distributions. The Maximum Likelihood Estimation procedure is used to estimate the parameters of the distribution. R codes are developed to implement the estimation procedure. A simulation study is carried out to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A smaller value of AIC and BIC indicates a better fit, and hence, T ET L fit the data better than ET L or Gaussian distributions. Devika et al (2016) used Esscher transformed Laplace distribution in modeling microarray data as an alternative to normal and Laplace distribution. In this work, we have proposed a new statistical model for the distribution of differential gene expression, which is a heavy tailed generalization of Laplace distribution.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller value of AIC and BIC indicates a better fit, and hence, T ET L fit the data better than ET L or Gaussian distributions. Devika et al (2016) used Esscher transformed Laplace distribution in modeling microarray data as an alternative to normal and Laplace distribution. In this work, we have proposed a new statistical model for the distribution of differential gene expression, which is a heavy tailed generalization of Laplace distribution.…”
Section: Applicationmentioning
confidence: 99%
“…After normalization, gene expression distribution (log ratio of red and green intensity measurements) which is referred to as error distribution has heavier tails than Gaussian distribution and has asymmetry of varying degrees. The error distribution is modeled using several densities, Devika et al (2016) used Esscher transformed Laplace distribution in modeling microarray data as an alternative to normal and Laplace distribution. Various authors suggested error distribution for gene expression data, asymmetric Laplace distribution (Purdom and Holmes, 2005), asymmetric type II compound Laplace , slash distribution with normal kernel (Punathumparambath, 2011), asymmetric slash Laplace (Punathumparambath, 2012a), skew slash t (Punathumparambath, 2012b), Laplace mixture (Punathumparambath and Kannan, 2012), slash distribution with Cauchy kernel (Punathumparambath, 2013), Double Lomax (Punathumparambath and Kulathinal, 2015) and compound exponential power (Punathumparambath, 2020).…”
Section: Introductionmentioning
confidence: 99%